Add-on prolonged-release melatonin for cognitive function and sleep in mild to moderate Alzheimer’s disease: a 6-month, randomized, placebo-controlled, multicenter trial - Wade, Alan G (Dove Medical Press, 2014)
PURPOSE: A link between poor sleep quality and Alzheimer’s disease (AD) has recently been suggested. Since endogenous melatonin levels are already reduced at preclinical AD stages, it is important to ask whether replenishing the missing hormone would be beneficial in AD and whether any such effects would be related to the presence of sleep disorder in patients. PATIENTS AND METHODS: The effects of add-on prolonged-release melatonin (PRM) (2 mg) to standard therapy on cognitive functioning and sleep were investigated in 80 patients (men [50.7%], women [49.3%], average age 75.3 years [range, 52–85 years]) diagnosed with mild to moderate AD, with and without insomnia comorbidity, and receiving standard therapy (acetylcholinesterase inhibitors with or without memantine). In this randomized, double-blind, parallel-group study, patients were treated for 2 weeks with placebo and then randomized (1:1) to receive 2 mg of PRM or placebo nightly for 24 weeks, followed by 2 weeks placebo. The AD Assessment Scale–Cognition (ADAS-Cog), Instrumental Activities of Daily Living (IADL), Mini–Mental State Examination (MMSE), sleep, as assessed by the Pittsburgh Sleep Quality Index (PSQI) and a daily sleep diary, and safety parameters were measured. RESULTS: Patients treated with PRM (24 weeks) had significantly better cognitive performance than those treated with placebo, as measured by the IADL (P=0.004) and MMSE (P=0.044). Mean ADAS-Cog did not differ between the groups. Sleep efficiency, as measured by the PSQI, component 4, was also better with PRM (P=0.017). In the comorbid insomnia (PSQI ≥6) subgroup, PRM treatment resulted in significant and clinically meaningful effects versus the placebo, in mean IADL (P=0.032), MMSE score (+1.5 versus −3 points) (P=0.0177), and sleep efficiency (P=0.04). Median ADAS-Cog values (−3.5 versus +3 points) (P=0.045) were significantly better with PRM. Differences were more significant at longer treatment duration. PRM was well tolerated, with an adverse event profile similar to that of placebo. CONCLUSION: Add-on PRM has positive effects on cognitive functioning and sleep maintenance in AD patients compared with placebo, particularly in those with insomnia comorbidity. The results suggest a possible causal link between poor sleep and cognitive decline.